2016
DOI: 10.1021/jacs.5b11708
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of the EutT Adenosyltransferase from Salmonella enterica: Mechanism of Four-Coordinate Co(II)Cbl Formation

Abstract: EutT from Salmonella enterica is a member of a class of enzymes termed ATP:Co(I)rrinoid adenosyltransferases (ACATs), implicated in the biosynthesis of adenosylcobalamin (AdoCbl). In the presence of co-substrate ATP, ACATs raise the Co(II)/Co(I) reduction potential of their cob(II)alamin [Co(II)Cbl] substrate by >250 mV via the formation of a unique four-coordinate (4c) Co(II)Cbl species, thereby facilitating the formation of a “supernucleophilic” cob(I)alamin intermediate required for the formation of the Ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(70 citation statements)
references
References 44 publications
6
64
0
Order By: Relevance
“…3B). The spectral changes are similar to those reported previously for the Lactobacillus reuteri ATR (31) and are consistent with the formation of a 4-coordinate cob(II)alamin species lacking an axial water ligand (32,33). The EPR spectrum of cob(II)alamin (Fig.…”
Section: Gtp/gdp Are Allosteric Ligands Of Atr-purified C Metal-supporting
confidence: 89%
“…3B). The spectral changes are similar to those reported previously for the Lactobacillus reuteri ATR (31) and are consistent with the formation of a 4-coordinate cob(II)alamin species lacking an axial water ligand (32,33). The EPR spectrum of cob(II)alamin (Fig.…”
Section: Gtp/gdp Are Allosteric Ligands Of Atr-purified C Metal-supporting
confidence: 89%
“…Previously, the mechanisms by which the CobA-type ACAT from Salmonella enterica , 31,32 the PduO-type human ACAT, 33 Lr PduO, 34 and the EutT-type ACAT from Salmonella enterica 35,36 can overcome the thermodynamically challenging Co(II) → Co(I)rrinoid reduction were investigated using magnetic circular dichroism (MCD) and electron paramagnetic resonance (EPR) spectroscopies. These studies led to the proposal that the ACAT/ATP complexes convert Co(II)rrinoids to effectively four-coordinate, square-planar species, thereby stabilizing the redox-active Co 3d z 2 -based molecular orbital (MO) and raising the reduction potential into the physiologically accessible range.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic and kinetic characterizations of EutT variants with a single alanine substitution within this motif indicated that these residues are critical for the uptake of divalent metal ions [M(II)] and the formation of 4c Co(II)Cbl. 18,19,35 For example, EutT C80A was found to be unable to convert Co(II)Cbl to AdoCbl both in vivo and in vitro , which has been shown in a subsequent spectroscopic study to reflect the inability of this variant to bind Co(II)Cbl. 18 Similarly, EutT C83A and EutT H67A did not support ethanolamine catabolism, though low in vitro activity was observed.…”
mentioning
confidence: 89%
“…18,19,35 For example, EutT C80A was found to be unable to convert Co(II)Cbl to AdoCbl both in vivo and in vitro , which has been shown in a subsequent spectroscopic study to reflect the inability of this variant to bind Co(II)Cbl. 18 Similarly, EutT C83A and EutT H67A did not support ethanolamine catabolism, though low in vitro activity was observed. In contrast, the EutT C79A variant retained most of the activity displayed by the wild-type enzyme.…”
mentioning
confidence: 89%